Prognostic value of pathological characteristics of invasive margins in early-stage squamous cell carcinomas of the uterine cervix - Surapan Khunamornpong (2018)
Background: To evaluate the pathological characteristics of invasive margins in early-stage cervical squamous cell carcinomas and their association with other clinicopathological features including clinical outcomes. Materials and Methods: Patients with FIGO stage IB-IIA cervical squamous cell carcinomas who received surgical treatment and had available follow-up information were identified. Their histological slides were reviewed for prognostic variables including tumor size, grade, extent of invasion, lymphovascular invasion, involvement of vaginal margin or parametrium, and lymph node metastasis. The characteristics of invasive margins including invasive pattern (closed, finger-like, or spray-like type), degree of stromal desmoplasia, and degree of peritumoral inflammatory reaction were evaluated along the entire invasive fronts of tumours. Associations between the characteristics of invasive margins and other clinicopathological variables and disease-free survival were assessed. Results: A total of 190 patients were included in the study with a median follow-up duration of 73 months. Tumour recurrence was observed in 18 patients (9%). Spray-like invasive pattern was significantly more associated as compared with closed or finger-like invasive pattern (p=0.005), whereas the degree of stromal desmoplasia or peritumoral inflammatory reaction was not. Low degree of peritumoral inflammatory reaction appeared linked with lymph node metastasis (p=0.021). In multivariate analysis, a spray-like invasive pattern was independently associated with marked stromal desmoplasia (p=0.013), whilst marked desmoplasia was also independently associated with low inflammatory reactions (p=0.009). Furthermore, low inflammatory reactions were independently associated with positive margins (p=0.022) and lymphovascular invasion (p=0.034). The patients with spray-like invasive pattern had a significantly lower disease-free survival compared with those with closed or finger-like pattern (p=0.004). Conclusions: There is a complex interaction between cancer tissue at the invasive margin and changes in surrounding stroma. A spray-like invasive pattern has a prognostic value in patients with early-stage cervical squamous cell carcinoma.